Evidence from a systematic review on first-time fathers' mental health and wellbeing needs. (2nd April 2019) - Baldwin, Sharin; Bick, Debra
Abstract : While the importance of addressing maternal mental health needs are more widely recognised, with routine mental health screening and assessment offered to women during and after pregnancy, men who have been asked about their experiences of parenthood report feeling marginalised and unacknowledged by health professionals during the perinatal period, and a lack of appropriate information on pregnancy, birth, child care, and balancing work and family responsibilities. This article considers the findings of a recent systematic review on first time fathers' mental health and wellbeing needs, and discusses practice implications for health visiting services.